2021
DOI: 10.1186/s12909-021-02585-z
|View full text |Cite
|
Sign up to set email alerts
|

Feedback after OSCE: A comparison of face to face versus an enhanced written feedback

Abstract: Background The Objective Structured Clinical Exam (OSCE) is a useful means of generating meaningful feedback. OSCE feedback may be in various forms (written, face to face and audio or video recordings). Studies on OSCE feedback are uncommon, especially involving Asian medical students. Methods We compared two methods of OSCE feedback delivered to fourth year medical students in Malaysia: (i) Face to face (FTF) immediate feedback (semester one) (ii)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…This seems to be agreeable with the suggestion of Black and McCormick (2010) that greater emphasis be placed on oral feedback as opposed to written feedback because oral or face to face feedback creates opportunities for the students to dialogue with the examiners. On the other hand, it disagrees with the report of Ngim et al (2021) who observed that students preferred individualized written feedback. Whether written or verbal, the important thing is that it should be individualized and this fact was corroborated by the report of Mulliner and Tucker (2015) that students preferred individualized verbal and written feedback.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…This seems to be agreeable with the suggestion of Black and McCormick (2010) that greater emphasis be placed on oral feedback as opposed to written feedback because oral or face to face feedback creates opportunities for the students to dialogue with the examiners. On the other hand, it disagrees with the report of Ngim et al (2021) who observed that students preferred individualized written feedback. Whether written or verbal, the important thing is that it should be individualized and this fact was corroborated by the report of Mulliner and Tucker (2015) that students preferred individualized verbal and written feedback.…”
Section: Discussioncontrasting
confidence: 86%
“…Concerning the timing of the feedback, research advocates that feedback is only useful to students when it is given in a timely manner (Lowe & Shaw, 2019;Mulliner & Tucker, 2015;Ngim et al, 2021). In this study, almost two-third (63.75%) of the examiners reported that the feedback was given immediately or soon after the OSCE.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations